Leveraging Artificial Intelligence (AI) in the growth of Fintech in Banking - Mehta, Apurva; Hashmi, Sadaf (My University, 2025)
The paper explores the use of artificial intelligence (AI) in the emerging fintech segment of the banking industry. It provides an insight of the current landscape of the banking industry and the challenges faced by traditional banks in adopting AI. The paper also explores the potential benefits of using AI in the banking fintech segment, including enhanced customer experience, increased resource optimisation, and enhanced loss prevention. The increase in the international investors segment of liquidity providers in the Indian capital markets make it imperative to study and better appreciate the role AI plays in various avenues of the financial services segment. The paper investigates the different applications of AI in the banking fintech segment, including chatbots, robo-advisors, fraud detection, and credit scoring. It also assesses the impact of AI on the workforce, customer trust, and regulatory compliance. The prominent role that corporate governance plays in the current business environment in effect dovetails work conducted by market practitioners in the banking domain in recent times. The findings indicate that the use of AI in the banking fintech segment is still in its nascent stages, but it has the probability to transform the industry. However, there are also concerns around the ethical implications of AI,including bias and lack of transparency. One other aspect that also needs to be considered is that with the application of AI does not in any way preclude the role human judgement and emotions play in certain crucial banking and credit / investment related decisions. The paper concludes by providing recommendations for banks and fintech companies on how to effectively implement AI in the banking fintech segment while addressing the ethical concerns. It also identifies areas for future research, including the incidence of AI on financial inclusion and the role of regulators in ensuring the responsible use of AI in the banking industry. The information gathered as well as the research conducted while preparing this paper also highlights the importance of AI tools in monitoring white collar crimes. Certain areas in forensic accounting and cyber-crime with specific interventions from the AI world make it a compelling case for detailed analysis of behaviour traits of those indulging in such acts.
ISME
Keywords: Artificial Intelligence (AI); Banking; Fintech; RBI; resource optimisation; loss prevention